CORRELATION OF STRUCTURE AND FUNCTIONAL DEFECT WITH QUALITY OF LIFE IN PATIENT WITH GLAUCOMA - Rahma An Nazzila, Meta; Jati, Krisna Dwi Purnomo; Ekantini, Retno; Gani, Tatang Talka (Majalah Oftalmologi Indonesia, 2024)
Introduction: Glaucoma damage generally produces a characteristic change in the morphology of the optic nerve, runs progressively and permanently that cause visual changes, decreased vision, and blindness. Blindness will affect one’s dependence to get help in their daily activities. This paper investigate the correlation between VFI, BCVA, MD and RNFL thickness with the quality of life of people with glaucoma using Glaucoma Quality of Life-15 (GQL-15).                                                           Methods: A cross-sectional study conducted at the Sardjito Eye Center in April 2021. Purposive sampling used to recruit glaucoma patients who had BCVA, Visual Field examination (Humphrey Field Analyzer (HFA) 3 Carl Zeiss Meditec Inc.), and OCT ONH (Cirrus HD-OCT 5000, Carl Zeiss). Glaucoma Quality of Life-15 (GQL-15) questionnaire were used to interview the patients.                                                                               Results: Eight (32%) normotension glaucoma and 17 (68%) open angle glaucoma patients were included. Fifteen (60%) patients aged 17-40 y.o, 7 (28%) aged 41-60 y.o and 3 (12%) aged > 60 y.o were included. Majority of the samples 6 of them were unemployed (24%), 5 entrepreneurs 5 (20%) and 5 students (20%). GQL-15 score was significantly correlated with respondent's BCVA r= -0.39 (p= 0.05). However, there was no correlation between GQL-15 with RNFL r= 0.01 (p=0.94), VFI r= -0.21 (p= 0.29) and MD with r=0.09 (p= 0.66) respectively. It showed that VFI and GQL-15 has negative correlation with a correlation coefficient of -0.21 (p=0.29). Subscale score related to central and near was significantly correlated with VFI (p= 0,05) and MD (p= 0,03).                   Conclusion: There was  a significant correlation between GQL-15 subscale score of central and near vision with VFI and MD. Subjects with lower VFI and MD tend to have worse problem with central and near vision. Total GQL-15 score has a weak negative correlation with BCVA and MD. There was no correlation between GQL-15 with VFI and RNFL.